2012
DOI: 10.1002/pssb.201200115
|View full text |Cite
|
Sign up to set email alerts
|

The effect of shock wave compression on double wall carbon nanotubes

Abstract: Double wall carbon nanotubes (DWCNTs) have proven to have a very good structural stability when exposed to high static pressures. We report here on the study of DWCNTs after application of shock wave (dynamic) compression up to 36 GPa in a recovery assembly. TEM images of so‐treated samples reveal a threshold between 19 and 26 GPa of shock wave compression above which significant structural damage is induced whereas only minor damage can be detected below. The threshold detected with TEM coincides well with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…By averaging over samples having d in varying from 0.5 to 1.9 nm, some experimental studies proposed that geometrical changes happen already at pressures as low as 3 GPa [35], and the response is elastic up to pressure of at least 10 GPa [36]. Other dynamic high-pressure experiments found that only minor tube structure damage occurs below 19 GPa, with the collapse of the double-wall CNT occurring at $ 26 GPa [37]. However, other works which considered similar diameter distributions reported collapse or large structural modifications at different pressures ranging from $ 13e15 GPa [18,38] to $ 25 GPa [17,39].…”
Section: Introductionmentioning
confidence: 99%
“…By averaging over samples having d in varying from 0.5 to 1.9 nm, some experimental studies proposed that geometrical changes happen already at pressures as low as 3 GPa [35], and the response is elastic up to pressure of at least 10 GPa [36]. Other dynamic high-pressure experiments found that only minor tube structure damage occurs below 19 GPa, with the collapse of the double-wall CNT occurring at $ 26 GPa [37]. However, other works which considered similar diameter distributions reported collapse or large structural modifications at different pressures ranging from $ 13e15 GPa [18,38] to $ 25 GPa [17,39].…”
Section: Introductionmentioning
confidence: 99%
“…The defect density is generally quantified by the D‐band over G‐band intensity ratio ( I D /I G ). The I D / I G data for the source and recovered materials together with previously reported results on DWCNTs exposed to 36 GPa of dynamic compression are presented in Table . Raman spectra of DWCNTs shocked to this pressure exhibit features similar to the spectra of SWCNTs subjected to the similar treatment in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows a schematic view of the shock wave assembly used in the dynamic compression experiments. The details of the experimental procedure can be found elsewhere . The samples were compressed by a stepwise shock and a new sample was loaded for each experiment (i.e., for each shock pressure) but always from the same source batch.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CNT powder was compressed (1.3 g cm −3 ) and placed into a stainless steel recovery assembly of planar geometry . The SWCNTs were exposed to 52 GPa of shock wave compression (the correspondent ramp temperature is estimated at 1496 K).…”
Section: Methodsmentioning
confidence: 99%